Upaya Meningkatkan Keterampilan Berpikir Logis dengan Pendekatan Inkuiri - Ainyn, Qurrota; Lutfi, Achmad; Hermynyawati, Emy (Jurnal Riset Pendidikan Kimia (JRPK), 2024)
This research aims to improve students' logical thinking skills in chemistry through an inquiry approach. The research method used is classroom action research by applying the Kemmis and McTaggart models. The research subjects were 35 students of XI MIPA 4 at SMAN 1 Manyar Gresik. Data was collected using a logical thinking skill assessment sheet consisting of deductive and inductive thinking components. The results showed that before the intervention, students could think logically with an average of 61.19, with a deductive component of 64.286 and an inductive component of 58.1. After applying a variety of learning models with an inquiry approach, there was an increase in students' logical thinking skills. In the cycle, the average logic thinking skills score increased to 76.9, with a deductive component of 81.43 and an inductive component of 72.38. In cycle II, there was a further increase. The average logical thinking skill reached 87.1, a deductive of 91.05, and an inductive of 83.15. Based on the results of this study, it inferred that variations in learning models with an inquiry approach show an increase in students' logical thinking skills in chemistry learning. Learning models such as POGIL and the 5E learning cycle encourage students to actively participate in the learning process and build a strong understanding of chemical concepts